Determination of Appropriate Overhead Line Insulator in Sumatra due to Contamination Severity - Arpan Zaeni; Umar Khayam; Deny Viviantoro (IAES Indonesia Section, 2019)
Insulator is one of the important equipment to support electrical power delivery which flow through the transmission line. Considering its very important role, the selection of insulators must be certainly based on deep analysis so that the insulator we choose works properly. There are several standards that can be used in selecting isolators, but in this paper the standards that will be used for case study analysis are IEC and IEEE standards. Case studies that will be used for the selection of insulators are for Sumatra that located in Indonesia which is a tropical country and certainly has special environmental characteristics that can influence the selection parameters of an insulator. There are several parameters that are commonly used in selecting overhead isolators those are power frequency voltage, environmental condition (contamination), switching over voltage, and lightning over voltage. Using environmental condition, it is found that the pollution category of Sumatra area is heavy, which influence the selection of insulation material.